2013
DOI: 10.1007/s11665-013-0672-2
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Debonding Monitoring of Composite Repaired Materials via Electrical, Acoustic, and Thermographic Methods

Abstract: Electrical properties of composite materials have been thoroughly investigated recently for the detection and monitoring of damage in Carbon Fibre Reinforced Polymers (CFRPs) under mechanical loading. Carbon Nanotubes (CNTs) are incorporated in the polymer matrix of CFRPs for the enhancement of their electrical properties. The electrical properties have shown to be sensitive to the damage state of the material and hence their monitoring provides the profile of their structural deterioration. The aim of the pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…A combination of techniques can be used either as a validation method for one or the other, as a benchmark, or the increased evidence of indications can be explored for a more detailed description of damage, for example by data fusion (327,328). Combinations reported include, among others, DSPI, X-ray CT and TSA (317); ultrasonic C-scan and shearography (318); ultrasound, thermography, vibration testing and embedded sensors (319); IRT and AE (329); IRT and DSPI (330); AE, ESPI and Superconducting Quantum Interference Device (SQUID) current mapping (331), and Electrical Potential Change method, AE and Lock-in Thermography applied to debonding monitoring of composite repairs (332). Combinations of NDT or NDE methods and their application raise two important issues.…”
Section: Comparisons and Combinations Of Ndt Methodsmentioning
confidence: 99%
“…A combination of techniques can be used either as a validation method for one or the other, as a benchmark, or the increased evidence of indications can be explored for a more detailed description of damage, for example by data fusion (327,328). Combinations reported include, among others, DSPI, X-ray CT and TSA (317); ultrasonic C-scan and shearography (318); ultrasound, thermography, vibration testing and embedded sensors (319); IRT and AE (329); IRT and DSPI (330); AE, ESPI and Superconducting Quantum Interference Device (SQUID) current mapping (331), and Electrical Potential Change method, AE and Lock-in Thermography applied to debonding monitoring of composite repairs (332). Combinations of NDT or NDE methods and their application raise two important issues.…”
Section: Comparisons and Combinations Of Ndt Methodsmentioning
confidence: 99%
“…1) has been widely employed in the past in various modes to characterize and analyse the response of materials during cyclic mechanical loading. Thermomechanical coupling by LT or the so called Thermoelastic Stress Analysis (TSA) [3,8,15,16,[22][23][24][25], has been used to construct stress maps for both composite and metal materials under cyclic mechanical loading. Stress maps allow for the determination of the location of damage initiation and its subsequent evolution.…”
Section: Thermomechanical Couplingmentioning
confidence: 99%
“…In this work, thermomechanical coupling was compared with simultaneously recorded acoustic emission signals. In a later study of the team, Grammatikos et al [15], the thermomechanical coupling observed in bonded repaired composites was studied in comparison with both acoustic emission signals and electrical measurements. More recently, the same principle was used in combination with Lamb waves technique, to study the bonded repair integrity of a patch repaired real helicopter wing by AgustaWestland (SW-4) [25].…”
Section: Thermomechanical Couplingmentioning
confidence: 99%
See 2 more Smart Citations